Hydrothermal synthesis and photocatalytic activities of stabilized bismuth vanadate/bismuth tungstate composites. Issue 2 (April 2018) - Ketwong, Pradudnet; Takashima, Mai; Nitta, Akio; Pookmanee, Pusit; Ohtani, Bunsho
Graphical abstract: Highlights: Bismuth vanadate/bismuth tungstate (BVO/BWO) composites were synthesized by various BVO fractions. Photocatalytic oxygen liberation was depended on BVO fractions and calcination. BVO particles were stabilized on BWO even calcination. Calcined BVO/BWO showed photocatalytic enhancement under visible light over BVO. Conduction band-bottom position of BVO/BWO was similar to BVO. Abstract: Bismuth vanadate/bismuth tungstate (BVO/BWO) composites in various BVO fractions ( f (V)) were synthesized through hydrothermal reaction. Morphology analysis of the composites showed that rod-like BVO structures were partially deposited on flake-ball (FB) BWO particles. In addition, surface structures of BWO, BVO and BVO/BWO were studied in energy-resolved distribution of electron traps and conduction band-bottom (CBB) position by household reversed double-beam photoacoustic spectroscopy (PAS) and single-beam PAS, respectively. Apparent CBB of BVO/BWO was ca. 0.4 eV anodically shifted from BWO and almost similar to BVO. Moreover, photocatalytic oxygen liberation under irradiation of UV–vis and visible lights demonstrated that photocatalytic activities of the BVO/BWO composites were depended on f (V) and calcined BVO/BWO composites in which BVO was stabilized on BWO showed enhancement of photocatalytic activity comparing to a pristine BVO. The prolonged and the highest active photocatalyst under visible light was calcined 0.80 f (V)due to BVO stabilization on FB-BWO particles.